Romania Toward a Low Carbon and Climate Resilient Economy : Better Use of Revenues from Auctioning European Union ETS Carbon Allowances for Climate Finance Programs in Non-ETS Sectors - World Bank (World Bank, Washington, DC, 2016)
Romanian industrial and power installations entered the European Union Emissions Trading Scheme (EU ETS) in 2007 when Romania joined the European Union. Emissions from aircraft operators were included in 2012. Around 200 Romanian installations and operators currently participate in the European Union Emissions Trading Scheme (EU ETS), out of a total of some 10,000, and they emitted around 40 percent of Romanian greenhouse gases in 2013. By the end of 2014, Romania collected about 260 million Euros from the EU ETS auctioning revenues, of which 71 percent was dedicated to climate finance projects. Potential EU ETS auctioning revenues for Romania could amount to around 4 billion per year by 2030. As the government strives for a climate resilient, low-carbon economy by 2030, the efficient use of revenues from the auctioning of EU ETS allowances could be an effective tool for reaching this goal in the sectors not covered by existing climate finance mechanisms and policy regulations. The introduction of a Market Stability Reserve (MSR) in 2018 is expected to increase significantly the carbon price. To conclude, in order to constitute a viable and longer-term climate finance programs supported by EU ETS auctioning revenue, it is necessary to amend the current legislation and approve an updated financial and organizational scheme for the use of EU ETS revenues.